Polyurethane based thermal interface material
The thermal interface material composition, featuring a urethane-based barrier and high aluminum hydroxide content, addresses the challenges of achieving high thermal conductivity and weather resistance in battery-powered vehicles, while being cost-effective and passing aging tests.
Patent Information
- Application Number
- JP2024226380
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2019-04-05
- Filing Date
- 2024-12-23
- Publication Date
- 2025-04-30
AI Technical Summary
Current thermal interface materials (TIMs) used in battery-powered vehicles face challenges in achieving high thermal conductivity, cost-effectiveness, ease of use, and weather resistance, particularly when using high amounts of aluminum hydroxide (ATH) as a filler.
A thermal interface material composition comprising a urethane-based barrier containing a non-reactive polyurethane prepolymer and 80-95% by weight of aluminum hydroxide (ATH), where the polyurethane prepolymer is the reaction product of a polyisocyanate and a polyol, with residual isocyanate groups less than 0.8% by weight.
The proposed TIM composition achieves high thermal conductivity, cost-effectiveness, improved weather resistance, and passes aging tests, including climate cycle bleeding tests, while maintaining a high percentage of ATH for enhanced thermal performance.
Smart Images

Figure 2025069122000001 
Figure 2025069122000002 
Figure 2025069122000003
Abstract
Description
[Technical field]
[0001] The present disclosure relates to thermal interface materials and their use in battery powered vehicles. [Background technology]
[0002] Compared to traditional means of transportation, battery-powered vehicles have many advantages, such as light weight and reduced CO2 emissions. However, there is still much work to be done to ensure optimal use of the technology. Many technical problems need to be overcome to achieve this. For example, One of these is to increase the driving range of battery-powered vehicles by developing high-density batteries. This, in turn, necessitates the development of better thermal management systems for high-density batteries. This leads to the importance of
[0003] In battery-powered vehicles, battery cells or modules are cooled by thermal interface materials (TIMs). Such TIMs are typically filled with thermally conductive fillers. It is made of a polymer-based material containing nitrogen to achieve a thermal conductivity of 2 W / m K or more. Filler with thermal conductivity of 100 W / m K or more, such as boron nitride or aluminum powder, is used. However, such fillers are expensive and abrasive. A cheaper, non-abrasive alternative is aluminum hydroxide (ATH). Approximately 10 W / m K Due to its low thermal conductivity, a high amount of ATH (i.e., 80% by weight or more) is required. In order to make it easier to use, liquid-based polymer binders (e.g., polyvinyl chloride) are used. However, such TIMs (high loading ATH) are typically used. Filled with liquid binders) tend to fail aging tests, i.e. weather It has been found that cracks tend to form after exposure to changing conditions. Summary of the Invention [Means for solving the problem]
[0004] Therefore, it has high thermal conductivity, is cost-effective, easy to use and weather resistant. There remains a need to develop a TIM that has
[0005] a) a urethane-based base comprising at least one non-reactive polyurethane prepolymer; and b) about 80 to 95 weight percent aluminum hydroxide. A composition comprising at least one non-reactive component, the total weight of the composition totaling 100% by weight. The polyurethane prepolymer comprises: i) at least one polyisocyanate and at least one ii) is a reaction product of an isocyanate derivative having aliphatic monol groups and substantially free of residual isocyanate groups; iii) an average molecular weight of 2,000 to 50,000 g / mol, When polyol-based materials are present in the composition, the content of the polyol-based materials is preferably urethane-based. The compositions provided herein have a total binder content of less than the total binder content of the base.
[0006] In one embodiment of the thermal interface material composition, the urethane-based binder component of the composition It is present at a level of about 2-20% by weight based on total weight.
[0007] In a further embodiment of the thermal interface material composition, at least one non-reactive polyurethane polymer is included. The copolymer comprises, based on the weight of at least one non-reactive polyurethane prepolymer. Contains less than about 0.8% by weight of residual isocyanate groups.
[0008] In yet another embodiment of the thermal interface material composition, at least one non-reactive polyurethane is The prepolymer is a mixture of at least one aliphatic polyisocyanate and at least one aliphatic It is a reaction product with monols.
[0009] In yet another embodiment of the thermal interface material composition, at least one aliphatic polyisocyanate is used. The diisocyanates are ethylene diisocyanate, hexamethylene-1,6-diisocyanate (HD I); isophorone diisocyanate (IPDI); 4,4'-, 2,2'-, and 2,4 '-Dicyclohexylmethane diisocyanate (H12MDI); Norbornene diisocyanate anates; 1,3- and 1,4-(bisisocyanatomethyl)cyclohexane (its cis or trans isomer); Tetramethylene-1,4-diisocyanate (TMXDI );1,12-dodecane diisocyanate;2,2,4-trimethylhexamethylene diisocyanate socyanates; and combinations of two or more thereof. It is a socyanate-based prepolymer.
[0010] In yet another embodiment of the thermal interface material composition, at least one aliphatic polyisocyanate is used. The ester is a prepolymer based on hexamethylene-1,6-diisocyanate (HDI). be.
[0011] In yet another embodiment of the thermal interface material composition, the urethane-based binder component is a non- Optionally, at least one other polyurethane different from the reactive polyurethane prepolymer is added. In this case, the at least one non-reactive polyurethane prepolymer and at least The weight ratio with at least one other polyurethane ranges from about 100:0 to 15:85.
[0012] In yet another embodiment of the thermal interface material composition, the aluminum hydroxide has a thickness of about 5-100 μm. The average particle size ranges from 0.1 to 1.0 μm.
[0013] In yet another embodiment of the thermal interface material composition, the aluminum hydroxide has a multimodal particle size. It has a squared distribution.
[0014] Further provided herein is an article comprising the thermal interface material composition described above.
[0015] In one embodiment, the article is a battery formed from one or more battery cells and a cooling unit. The battery module further includes a battery module connected to a cooling unit via a thermal interface material composition. To be continued. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0016] As used herein, a) a urethane composition comprising at least one non-reactive polyurethane prepolymer; b) a tungsten-based binder component; and c) about 80 to 95% by weight of aluminum hydroxide (ATH). ) wherein the total weight of the composition totals 100 wt %. If a polyol-based material is present in the composition, Heat-resistant, provided that the content is less than the total content of the urethane-based binder components. An interface material is disclosed.
[0017] As used herein, a non-reactive polyurethane prepolymer comprises at least one poly(ethylene glycol) copolymer. It is the reaction product of an isocyanate and at least one aliphatic monol. The non-reactive polyurethane prepolymers used are approximately 2,000 to 50,000 g / mol. , or about 3,000 to 30,000 g / mol, or about 4,000 to 15,000 g / m In addition, the non-reactive polyurethane prepolymers used herein have molecular weights in the range of 10 to 200 mol. The polymer is substantially free of residual isocyanate groups, i.e., the prepolymer contains about There are less than 0.8% by weight or less than about 0.4% by weight residual isocyanate groups.
[0018] According to the present disclosure, the polyisocyanates used herein are multifunctional isocyanates. are prepolymers based on isocyanates (e.g. diisocyanates and triisocyanates), The polyisocyanate may be aliphatic, cycloaliphatic, or aromatic. Exemplary polyfunctional isocyanates include, but are not limited to, ethylene diisocyanates. Hexamethylene-1,6-diisocyanate (HDI); Isophorone diisocyanate Anate (IPDI); 4,4'-, 2,2'-, and 2,4'-dicyclohexylmethanate Norbornene diisocyanate (H12MDI); Norbornene diisocyanate; 1,3- and 1 ,4-(bisisocyanatomethyl)cyclohexane (including its cis or trans isomers) );Tetramethylene-1,4-diisocyanate (TMXDI);1,12-dodecane di Isocyanates;2,2,4-Trimethylhexamethylene diisocyanate;2,2'- , 2,4'-, and 4,4'-methyldiphenyl diisocyanate (MDI); Carbodi Imide modified MDI; 2,4- and 2,6-toluene diisocyanate (TDI); 1,3 - and 1,4-phenylene diisocyanate; 1,5-naphthylene diisocyanate; Triphenylmethane-4,4',4”-triisocyanate; Polyphenylpolymethylenepolyisocyanate In one embodiment, the multifunctional isocyanates used herein include The isocyanate is an aliphatic isocyanate. In a further embodiment, the isocyanate used herein is The polyfunctional isocyanates used are hexamethylene-1,6-diisocyanate; isophorone Diisocyanates;1,3-(bisisocyanatomethyl)cyclohexane;1,4-(bisisocyanatomethyl)cyclohexane (isocyanatomethyl)cyclohexane; or a mixture of two or more thereof. In a further embodiment, the polyfunctional isocyanate used herein is hexamethylene -1,6-diisocyanate.
[0019] Polyisocyanates are used in amounts up to about 25%, or up to about 15%, or up to about 10%. For example, the percent NCO content may be about 1 to 10%, or about 3 to 5%. In certain embodiments, the polyisocyanates used herein may range from 100 to 800 ppm. at least about 2.0, or at least about 2.2, or at least about 2.4; and It may have an average isocyanate functionality of 4 or less, or about 3.5 or less, or about 3.0 or less. In further embodiments, the equivalent weight of the polyisocyanate is at least about 100, or at least and may be no more than about 300, or no more than about 250. It may be up to about 200 or less.
[0020] As used herein, an aliphatic monol is an alkyl group having a molecular weight of about 200 to 5,000 g / mol, or about 3 The copolymer may have a molecular weight of about 500 to 3,000 g / mol, or about 500 to 2,000 g / mol.
[0021] In preparing the non-reactive polyurethane prepolymer, polyisocyanate and aliphatic Additional additives may be added along with the monols. These include catalysts, chain extenders, crosslinkers, etc. These include bridgers, fillers, moisture scavengers, colorants, etc. In particular, many aliphatic and aromatic alkyl esters are amines (e.g. diaminobicyclooctane-DABCO), organometallic compounds (e.g. Djib dibutyltin dilaurate, dibutyltin diacetate), carboxylic acid and phenol alkyl Metal salts (calcium, magnesium, hexanoate, octanoate, naphthenate, linoleate) Salts of tungsten, strontium, and barium can be used as catalysts.
[0022] Furthermore, a non-reactive polyurethane prepolymer that is substantially free of residual isocyanate groups is provided. To obtain this, a stoichiometric excess of aliphatic monol must be used in the reaction. That is, the ratio of -OH groups in the aliphatic monol to -NCO groups in the polyisocyanate. The non-reactive polyurethane prepolymer is prepared by mixing at least one polyisocyanate. The cyanate, at least one aliphatic monol, and other additives such as catalysts are mixed together. The reaction mixture is mixed under nitrogen atmosphere or vacuum at about 20 to 80°C for about 10 to 60 minutes. Stir; cool the reaction mixture to room temperature; place the reaction mixture in a closed container. storing;
[0023] The urethane-based binder component is made of one or more of the non-reactive polyurethane prepolymers described above. Further, the urethane-based binder component may be formed from the polymer described above. Optionally, other suitable polyurethanes different from the non-reactive polyurethane prepolymers mentioned above may be used. In addition, one or more non-reactive polyurethane propanes may be included within the urethane-based component. The weight ratio between the copolymer and optional other polyurethanes is about 100:0 to 15:8. 5, or about 100:0 to 20:80, or about 100:0 to 25:75. can.
[0024] According to the present disclosure, the urethane-based binder component is at a level of about 2-20% by weight, or about 3-15% by weight, or about 5-15% by weight. It may be present in M.
[0025] As used herein, ATH refers to unimodal ATH powder as well as multimodal particle size distributions. The ATH powder may have a distribution (e.g., bimodal, trimodal, etc.). If a powder is used, the average particle size may range from about 5 to 100 μm. Also, when multimodal ATH powder is used, the average particle size of the smallest particles is about 10 μm. The average particle size of the largest particles may be greater than about 50 μm, while the average particle size of the largest particles may be less than about 50 μm. Additionally, the ATH powder used herein may be any of a variety of silanes, titanates, carboxylates, etc. The surface can also be treated with
[0026] According to the present disclosure, the ATH powder is about 80 to 95% by weight based on the total weight of the TIM composition. % or at a level of about 80-92% by weight of the composition.
[0027] Further, up to about 10% by weight, or about 1-10% by weight, or about 2-7% by weight, or about 2- 5% by weight of precipitated calcium carbonate can be added to the TIM composition. Without wishing to be bound by theory, the optional addition of precipitated calcium carbonate may improve the It is believed that anti-settling can be improved.
[0028] Additionally, the TIM compositions disclosed herein may contain additives such as catalysts, plasticizers, stabilizers, adhesion promoters, It may optionally further include other suitable additives such as fillers, colorants, etc. The optional additive may be present in an amount of up to about 10% by weight, or up to about 8% by weight, based on the total weight of the TIM; Or it may be present at a level up to about 5% by weight.
[0029] As shown in the following examples, high loadings of A were added to the non-reactive polyurethane prepolymer. By incorporating TH fillers, the TIM thus obtained has high thermal conductivity (e.g. 2 W / m K or higher) and improved weather resistance.
[0030] As used herein, a battery pack system, in which a cooling unit or plate The TIM is connected to a battery module (formed of one or more battery cells). The battery pack system further comprises: In one embodiment, a battery pack system is disclosed for use in a battery powered vehicle. do. EXAMPLES
[0031] material PU-Pre - Density of 1.040g / ml and viscosity (dynamic) of 1500mPa-s Methylene diphenyl diisocyanate (MDI) based urethane prepolymers having; Polyisocyanate – Hexamethylene-1,6-diisocyanate obtained from Covestro socyanate (HDI) homopolymer (HDI trimer); Monole - Obtained from DowDuPont and opened with C12-C14 fatty alcohols The fully propoxylated (containing propylene oxide) monol (MW93 5g / mol, OH number: 60.4, equivalent weight: 927); Available from DowDuPont under the trade name Voranol® 1010L Polyol-1-polypropylene oxide polyol (functionality: 2, MW: 1000 g / mol); Available from DowDuPont under the trade name Voranol® CP4610 Polyol-2-glycerin initiated ethylene oxide based propoxyl Fluorotriol (MW: 1800 g / mol, OH value: 35 KOH / g); ATH - Aluminium hydroxide with bimodal distribution and small average particle size is less than 10 μm, and the average particle size of the larger particles is more than 50 μm; ·CaCO3-precipitated calcium carbonate; Catalyst-1 – Dibutyl ether obtained from Evonik under the trade name DABCOTMT-12 Tin dilaurate (DBTDL); Catalyst-2 - Obtained from Momentive under the trade name FomrezTMUL28 Dimethyltin dineodecanoate; · Fatty acids - methyl esters of unsaturated C16-C18 fatty acids; Plasticizers - Di-C8~C10 alkyl esters of 1,2-benzenecarboxylic acid Phthalic acid obtained from DINP-Evonik under the trade name VestinolTM9 Di-isononyl; · Silane-Hexadecyltrimethoxysilane; PU (non-reactive) - a non-reactive polyurethane preform having the following formulation and properties (Table 1): The polymer is prepared by: 1) mixing polyisocyanate and monol in a reactor and heating the temperature to 60°C. 2) Catalyst-1 was added to the reaction mixture; 3) The mixture was heated at 80° C. for 45 h under a nitrogen atmosphere. 4) The reaction mixture was cooled to room temperature and placed in a sealed container. The mixture was prepared by transferring to a container.
[0032] [Table 1]
[0033] PU - Polyurethane having the following formulation and properties (Table 2) was prepared by 1) PU -Pre, polyol-2, and 1,4-butanediol are mixed and the temperature is increased to 60°C. 2) dissolving catalyst-2 in DINP and adding the dissolved catalyst-2 to the reaction mixture; 3) The mixture was stirred at 80° C. under nitrogen for 45 min, followed by stirring under vacuum for 10 min; The reaction mixture was cooled to room temperature and transferred to a sealed container.
[0034] [Table 2]
[0035] method Sample preparation In each of Comparative Examples CE1 to CE13 and Examples E1 to E14, Table 3 or Table 4 All ingredients listed in the formula (liquid ingredients first, then solid ingredients) are mixed in a planetary mixer. The mixture was placed in a centrifuge or double asymmetric centrifuge and mixed under vacuum for about 30 minutes. The resulting TIM ( The samples (in stock form) were transferred to cartridges, pails, or drums for storage.
[0036] Press-in force The compression force of the TIM paste for each sample was measured using a tensiometer (Zwick). The TIM paste from each sample was placed on a metal surface. The aluminum piston is placed on top of the sample paste, and the sample paste is then poured over the sample paste by 5 mm (initial thickness The sample paste was then compressed at a speed of 1 mm / s to a thickness of 0.3 mm. The specimen was further compressed and the force deflection curve was recorded. The force (N) at a thickness of 0.5 mm was defined as the press-in force. And recorded it.
[0037] Thermal Conductivity The thermal conductivity of the TIM paste obtained for each sample was calculated using the ZFW Stuttgart method. The thickness was measured according to ASTM 5470 using a TIM tester from Art. Absolute thermal conductivity λ (W / m K) in Spaltplus mode at 1.8-1.2 mm It was recorded.
[0038] resistivity The TIM paste obtained for each sample was molded into a test plate with a thickness of 2.0 mm, and the volume resistance was measured. Resistivity (Ω.cm) to DIN IEC 93 / VDE 0303 / HD 429 S1 Therefore, measurements were taken using these test plates at 100V and 23°C.
[0039] Cycle Bleeding Test For each sample, the structure was “e-coated steel substrate / TIM / glass.” The sandwich panels were fabricated using e-coated steel substrates. The TIM paste was then applied to the glass. The base material is compressed to 3.0 mm (adjust the thickness with a spacer) and the test sample is 60 mm in diameter. The test samples were then exposed to climatic conditions, with each cycle taking 12 hours to complete. It took 4 hours at -40°C (uncontrolled humidity) and 4 hours to adjust the temperature to 80°C. The sandwich was then assembled at 80°C for 4 h and 80% by weight relative humidity for 2 h. The panels were visually inspected after climatization and samples without crack formation, phase separation, and slippage were marked "o We rated them as “k” and the rest as “Nok”.
[0040] As shown in Comparative Examples CE1-CE2 and CE4-CE10 (Table 3), the high loading When a large amount of ATH (82-87 wt%) was added to the polyol-based binder, All of the TIM pastes tested failed both cycle bleeding tests (except for CE3). E3 passed the 1w cycle bleeding test, but failed the 2s cycle bleeding test Similarly, in CE11 to CE13 (Table 3), the binder material was an aromatic poly Non-reactive polyurethanes combined with urethanes (CE11) or high levels of polyols When changing to a tantalum prepolymer (CE12~CE13), the resulting TIM paste is also Both cycle bleeding tests failed.
[0041] On the other hand, as shown in Examples E1 to E14 (Table 4), the high loading of ATH (82-91% by weight) is mixed into a non-reactive polyurethane prepolymer-based binder. The resulting TIM paste maintains high thermal conductivity and does not bleed during both cycles. Passed the test (except E9 which only passed the 1w cycle bleeding test).
[0042] [Table 3]
[0043] [Table 4]
Claims
1. a) a urethane-based base containing at least one non-reactive polyurethane prepolymer; Indya components and b) about 80 to 95 weight percent aluminum hydroxide. 、 The total weight of the composition is 100% by weight in total, The at least one non-reactive polyurethane prepolymer comprises: i) at least one poly a reaction product of a reisocyanate and at least one aliphatic monol; and ii) a residual substantially free of isocyanate groups; and iii) having an average molecular weight of 2,000 to 50,000 g / mol, If a polyol-based material is present in the composition, the polyol-based The thermal interface material has a content of material less than the total content of the urethane-based binder component. Food composition.
2. The urethane-based binder component is about 2 to 20 parts by weight based on the total weight of the composition.
10. The thermal interface material composition of claim 1 , wherein the thermal interface material composition is present at a level of 0% by weight.
3. The at least one non-reactive polyurethane prepolymer is The residual yttrium is less than about 0.8% by weight based on the weight of the non-reactive polyurethane prepolymer. The thermal interface material composition of claim 1 comprising a sorbitol group.
4. The at least one non-reactive polyurethane prepolymer is The reaction product of an aliphatic polyisocyanate and at least one aliphatic monol.
2. The thermal interface material composition of claim 1.
5. The at least one aliphatic polyisocyanate is selected from the group consisting of ethylene diisocyanate; Dihexamethylene-1,6-diisocyanate (HDI); Isophorone diisocyanate (I PDI); 4,4'-, 2,2'-, and 2,4'-dicyclohexylmethane diisocyanate norbornene diisocyanate (H12MDI); 1,3- and 1,4-(bis isocyanatomethyl)cyclohexane (including its cis or trans isomers); 1,4-ethylenediisocyanate (TMXDI); 1,12-dodecane diisocyanate 2,2,4-trimethylhexamethylene diisocyanate; and two or more thereof A prepolymer based on a multifunctional isocyanate selected from the group consisting of The thermal interface material composition of claim 4 .
6. The at least one aliphatic polyisocyanate is hexamethylene-1,6-diisocyanate.
6. The thermal interface material composition of claim 5, which is a cyanate (HDI) based prepolymer. 。
7. The urethane-based binder component is a non-reactive polyurethane prepolymer. may optionally further comprise at least one other polyurethane different from said at least one non-reactive polyurethane prepolymer and said at least one The polyurethane composition according to claim 2, wherein the weight ratio with other polyurethanes is in the range of about 100:0 to 15:
85. A thermal interface material composition.
8. 4. The method of claim 1, wherein the aluminum hydroxide has an average particle size in the range of about 5 to 100 μm. Item 2. The thermal interface material composition of item 1.
9. 9. The thermal interface of claim 8, wherein the aluminum hydroxide has a multimodal particle size distribution. Surface material composition.
10. An article comprising the thermal interface material composition of claim 1.
11. The battery module further includes one or more battery cells and a cooling unit. The battery module is connected to the cooling unit via the thermal interface material composition. The article of claim 10.